2010
DOI: 10.1021/cg100706n
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Architectures in 5,5′-Substituted Hydantoins: Crystal Structures and Hirshfeld Surface Analyses

Abstract: A series of three 5,5′-substituted hydantoin derivatives (1−3) were synthesized, and their crystal structures were solved using single-crystal synchrotron/powder-crystal X-ray diffraction data with a detailed analysis of Hirshfeld surfaces and fingerprint plots facilitating a comparison of intermolecular interactions in building different supramolecular architectures. A comparison of supramolecular assembly in the compounds with that in similar 5,5′-substituted hydantoins in the Cambridge Structural Database (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 59 publications
(99 reference statements)
1
25
0
Order By: Relevance
“…The N1-C2-O2 bond angle 130.0 (2)°is greater than the N3-C2-O2 angle 123.2 (2)°. This difference is also observed in all 136 hydantoins derivative entries including the hydantoin molecule [40], and can be attributed to the fact the N3 atom shares its lone pair between the O2 and O4 atoms, while the N1 atom is involved in a π-resonance with the C2-O2 carbonyl group only [41]. The molecular structure and crystal packing of (I) are stabilized by N-H···O hydrogen bonds.…”
Section: Resultsmentioning
confidence: 89%
“…The N1-C2-O2 bond angle 130.0 (2)°is greater than the N3-C2-O2 angle 123.2 (2)°. This difference is also observed in all 136 hydantoins derivative entries including the hydantoin molecule [40], and can be attributed to the fact the N3 atom shares its lone pair between the O2 and O4 atoms, while the N1 atom is involved in a π-resonance with the C2-O2 carbonyl group only [41]. The molecular structure and crystal packing of (I) are stabilized by N-H···O hydrogen bonds.…”
Section: Resultsmentioning
confidence: 89%
“…Molecular Hirshfeld surfaces [42][43][44][45][46][47][48] in the crystal structure of MOC are determined based on the electron distribution calculated as the sum of spherical atom electron densities. 49,50 For a specified crystal structure and set of spherical atomic electron densities, the Hirshfeld surface is unique.…”
Section: Methodology Of Hirshfeld Surface Analysismentioning
confidence: 99%
“…As for the large amount of white region in dnorm surfaces, it is suggested that there is a weaker and farther contact between molecules, rather than hydrogen bonding. Figure 7 showed that the two-dimensional (2D) plots that were generated [87] …”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%
“…As for the large amount of white region in d norm surfaces, it is suggested that there is a weaker and farther contact between molecules, rather than hydrogen bonding. Figure 7 showed that the two-dimensional (2D) plots that were generated [87] correspond to the O···H, C···H and H···H interactions from the Hirshfeld surface of the coordination compound 1. With the help of these analysis results, different interactions can be separated from each other that would commonly overlap in full fingerprint plots.…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%